Peran Software Accurate dalam Meningkatkan Efisiensi Penyusunan Laporan Keuangan UMKM - Faradiana Cahyani Marina; Putri Dwi Aprilia Nur Khasanah (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2026)
This study aims to examine the role of Accurate software in improving the efficiency of financial statement preparation at UMKM XYZ, a client of Prima Accounting. The research is motivated by the persistence of manual and unsystematic bookkeeping practices that often lead to delays and errors in financial reporting. A descriptive qualitative approach was employed, with data collected through in-depth interviews with a staff member of Prima Accounting directly involved in the implementation and assistance process. The findings indicate that the use of Accurate software accelerates the reporting process, minimizes recording errors, and produces more structured and reliable financial statements. The efficiency achieved extends beyond time savings, contributing to improved information quality that supports managerial decision-making. These results highlight that the integration of accounting technology, supported by professional guidance, plays a significant role in strengthening sustainable financial governance in SMEs.